Some macroeconomic policy implications of consumer-oriented food subsidies - Siamwalla, Ammar (International Food Policy Research Institute, 1988)
This chapter presents a qualitative analysis of the macroeconomic effect of food subsidies. Other chapters in this book give findings arising out of empirical research. The task here is to provide some typologies so that countries other than those studied can discern the contexts in which questions and problems arise and can utilize the study findings for policy guidance.